Navigating White News Asian American Journalists at Work. - Oh, David C. (Rutgers University Press, 2023)
"Combining critical race studies with cultural production studies, Navigating White News: Asian American Journalists at Work is the only academic book to examine the ways that racial identification and activation matters in their understanding of news. This adds to the existing literature on race and the sociology of news by examining intra-racial differences in the ways they navigate and understand White newsrooms. Employing in-depth interviews with twenty Asian American journalists, who are actively working in large and small newsrooms across the United States, the book argues that Asian American reporters for whom racial identities are salient questioned what counted as news, questioned the implicitly White perspective of objectivity, and actively worked toward providing more complex, substantive coverage of Asian American communities. For Asian American reporters for whom racial identity was not meaningful, they were more invested in existing professional norms. Regardless, all journalists understood that news is a predominantly and culturally White institution"-- Provided by publisher.
Description based upon print version of record.
Keywords: Asian American journalists.; Journalism -- United States -- 21st century.; Reporters and reporting -- Social aspects -- United States.; Asian Americans -- Ethnic identity.; Asian Americans -- Race identity.; Asian Americans and mass media.; Mass media and race relations -- United States.; Asian American professional employees.; United States -- Race relations -- 21st century.; Américains d'origine asiatique -- Identité ethnique.; Américains d'origine asiatique et médias.; Médias et relations raciales -- États-Unis.; Professionnels salariés américains d'origine asiatique.; États-Unis -- Relations raciales -- 21e siècle.; SOCIAL SCIENCE / General.; Asian American professional employees; Asian Americans and mass media; Asian Americans -- Ethnic identity; Asian Americans -- Race identity; Journalism; Mass media and race relations; Race relations; Reporters and reporting -- Social aspects; United States; 2000-2099; asian, asian american, immigration migration, emigration, work, labor, journalism, journalists, race, racism, xenophobia, ethnicity, culture, microaggressions.; Electronic books.